2010
DOI: 10.1134/s0006297910040073
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties and structure of the lipopolysaccharide of a vaccine strain of Francisella tularensis generated by inactivation of a quorum sensing system gene qseC

Abstract: A knockout mutant with a deletion in a quorum sensing system gene qseC was generated from the vaccine strain Francisella tularensis 15 by site-directed mutagenesis. The variant with the inactivated gene qseC differed from the parental strain in growth rate on solid nutrient medium but had the same growth dynamics in liquid nutrient medium. The mutation abolished almost completely the resistance of the vaccine strain to normal rabbit serum and its ability to survive in macrophages; in addition, the strain lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…QseC has been previously reported to be an activator of virulence. It has been shown to positively regulate motility in EHEC O157, Salmonella, and UPEC (3,4,10,21,37,49,72), invasion in Salmonella (49), and overall virulence in many other pathogens (47,57,59,79). Here, we have shown that deletion of qseC significantly decreases formation of A/E lesions on HeLa cells and that the qseC mutant's ability to form these lesions is unaffected by epinephrine (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…QseC has been previously reported to be an activator of virulence. It has been shown to positively regulate motility in EHEC O157, Salmonella, and UPEC (3,4,10,21,37,49,72), invasion in Salmonella (49), and overall virulence in many other pathogens (47,57,59,79). Here, we have shown that deletion of qseC significantly decreases formation of A/E lesions on HeLa cells and that the qseC mutant's ability to form these lesions is unaffected by epinephrine (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…The bacterial strains used in these studies, E. coli O130 ( 26 ), Francisella tularensis 15 ( 27 ), A. baumannii 1053 ( 28 ), P. aeruginosa 2192 (a clinical isolate from a cystic fibrosis patient) ( 29 ), and B. mallei C-5 ( 30 ), were grown as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The distinctions in protective activity of the preparations and their ability to increase functional activity of white mice lymphocytes determined during the examination can be possibly caused by nucleotide polymorphism of the genes coding outer membrane proteins [8], and variability of LPS structure [9,10] in F. tularensis subspecies that undoubtedly affects on the bacteria virulence.…”
Section: Discussionmentioning
confidence: 99%